2014
DOI: 10.1021/am5067332
|View full text |Cite
|
Sign up to set email alerts
|

Microemulsion Systems for Fiber Deconstruction into Cellulose Nanofibrils

Abstract: A new method to produce cellulose nanofibrils (CNF) is proposed to reduce the energy demand during deconstruction of precursor fibers suspended in aqueous media. Microemulsions were formulated with aqueous solutions of urea or ethylenediamine and applied to disrupt interfibril hydrogen bonding. Compared to typical fibrillation of lignin-containing and lignin-free fibers, pretreatment with microemulsion systems allowed energy savings during microfluidization of 55 and 32%, respectively. Moreover, microemulsion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 25 publications
(40 reference statements)
0
41
0
Order By: Relevance
“…The average diameter size was 13 ± 8 nm, thereby corroborating the nanoscale of the fibrils obtained. Carrillo et al obtained similar size fibril bundles when preparing LCNF from Kraft digestion of eucalyptus using aqueous solutions of urea (Carrillo et al 2014). The nanopaper produced were observed by AFM and FE-SEM in order to measure roughness and observe surface structure.…”
Section: Morphology Of Lcnf and Nanopapermentioning
confidence: 97%
“…The average diameter size was 13 ± 8 nm, thereby corroborating the nanoscale of the fibrils obtained. Carrillo et al obtained similar size fibril bundles when preparing LCNF from Kraft digestion of eucalyptus using aqueous solutions of urea (Carrillo et al 2014). The nanopaper produced were observed by AFM and FE-SEM in order to measure roughness and observe surface structure.…”
Section: Morphology Of Lcnf and Nanopapermentioning
confidence: 97%
“…The maximum thermal decomposition temperature was 343 ∘ C, while it was 310 ∘ C for the CNFs prepared without the NaOH pretreatment. Since urea and ethylenediamine have the ability to loosen the hydrogen bonds and solubilize cellulose, they could be applied to pretreat cellulose [190]. Before further mechanical disintegration, a microemulsion (surfactant-oil-water systems) including urea or ethylenediamine was applied to treat kraft pulps.…”
Section: Solvent-assisted Pretreatmentsmentioning
confidence: 99%
“…Before further mechanical disintegration, a microemulsion (surfactant-oil-water systems) including urea or ethylenediamine was applied to treat kraft pulps. It was found that urea and ethylenediamine pretreatment could effectively accelerate the isolation of CNFs [190].…”
Section: Solvent-assisted Pretreatmentsmentioning
confidence: 99%
“…It has been shown that the presence of the charged groups bring about electrostatic repulsion and fibre swelling which reduces the effect of hydrogen bonding and hydrophobic interactions, thereby easing fibrillation (Nechyporchuk et al 2016a). In addition, a multicomponent microemulsion system containing either urea or ethylenediamine was used to ease the delamination of cellulose and lignocellulosic fibres (Carrillo et al 2014). The authors attributed the reduction in energy demand for CNF production to the ability of the microemulsion system to reduce the hydrogen bonding effect on cellulose.…”
Section: Introductionmentioning
confidence: 99%